The role of e-participation and open data in evidence-based policy decision making in local government. Issue 1 (2nd April 2016) - Sivarajah, U.; Weerakkody, V.; Waller, P.; Lee, H.; Irani, Z.; Choi, Y.; Morgan, R.; Glikman, Y.
ABSTRACT: The relationships between policies, their values, and outcomes are often difficult for citizens and policymakers to assess due to the complex nature of the policy lifecycle. With the opening of data by public administrations, there is now a greater opportunity for transparency, accountability, and evidence-based decision making in the policymaking process. In representative democracies, citizens rely on their elected representatives and local administrations to take policy decisions that address societal challenges and add value to their local communities. Citizens now have the opportunity to assess the impact and values of the policies introduced by their elected representatives and hold them accountable by utilizing historical open data that is publicly available. Using a qualitative case study in a UK Local Government Authority, this article examines how e-participation platforms and the use of open data can facilitate more factual, evidence-based, and transparent policy decision making and evaluation. From a theoretical stance, this article contributes to the policy lifecycle and e-participation literature. The article also offers valuable insights to public administrations on how open data can be utilized for evidence-based policy decision making and evaluation.